REGULASI PENGGUNAAN TEKNOLOGI ROBOTIK TELESURGERY DALAM PRAKTIK KEDOKTERAN - Karolin, Yolanda Nindiya; Mardijono, Adianto (IBLAM LAW REVIEW, 2024)
Technological developments in Indonesia are very rapid, especially in the field of artificial intelligence. The existence of artificial intelligence also has a major influence in the field of medical services. One form of service using remote robotic surgical technology is telesurgery. Telesurgery is a surgical operation that is perfomed remotely and this service is currently popular. In general, the regulation of telesurgery practice refers to Law of the Republic of Indonesia Number 29 of 2004 concerning Medical Practice and Law of the Republic of Indonesia Number 17 of 2023 concerning Health. Currently, Indonesia still does not have specific laws and regulations that regulate the practice of medical services using remote surgical methods. Because the practice of telesurgery in Indonesian has not been clearly regulated, it can be concluded that there are still problems in the use of telesurgery. Therefore, this research will discuss and analyze reguulations related to the use of robotic remote surgery technology. This research uses conventional legal methods and is based on a statutory and conceptual approach, then provides an analysis of the form of regulation for the use of telesurgical technology using robots in medical practice.